Techno-economic evaluation of a hybrid CSP + PV plant integrated with thermal energy storage and a large-scale battery energy storage system for base generation. (October 2018) - Zurita, Adriana; Mata-Torres, Carlos; Valenzuela, Carlos; Felbol, Carlos; Cardemil, José M.; Guzmán, Amador M.; Escobar, Rodrigo A.
Highlights: Techno-economic analysis of a hybrid CSP and PV power plant with TES and BESS. BESS inclusion to the hybrid plant results on an increase of the capacity factor. The battery bank cost accounts for most of the BESS costs. A reduction of 60–90% of the battery bank cost (300 USD/kWh) is required. A synergetic operation with both storage types under a cost reduction was found. Abstract: Chile presents a combination of favorable climatic conditions which result in the highest levels of solar irradiation in the world. In this paper, the performance of a hybrid CSP + PV plant at utility-scale integrated with a large-scale Battery Energy Storage System (BESS) located in northern Chile was studied. The model considered a solar power tower integrated with a two-tank molten salt direct TES and a fixed-angle PV plant coupled to a BESS to deliver a baseload of 100 MWe . A parametric analysis was carried out in terms of the PV size, solar multiple, TES hours capacity, and BESS size. The hybrid plant performance was studied in terms of the LCOE and the capacity factor. The minimum LCOE configurations were identified and a sensibility analysis was carried out to evaluate the effect of a cost reduction of the BESS in the hybrid plant configuration for different BESS sizes. Results showed that current investment costs of the storage section of the BESS make unprofitable its integration to the hybrid plant, so, it is required a reduction of approximately 60–90% of the storage cost (based on a reference value of 300 USD/kWh) to achieve competitive LCOEs in comparison to those obtained for a hybrid plant without BESS. Under this BESS cost reduction scenario, it was found a solutions domain with different hybrid plant configurations, which allow to integrate and complement the production of both CSP and PV plants with both storage types in a synergetic operation. Also, a comparative study evaluating the differences between implementing a fixed-tilt PV configuration or a one-axis tracking system in the hybrid plant scheme was carried out, obtaining that the annual production of the hybrid plant increases by no more than 5% with the tracking system, while the LCOE is reduced up to -1.98% due to a decrease of the BESS participation in the total output. These results indicate that the minimum LCOE configurations of a hybrid CSP + PV plant with tracked PV arrays (given a BESS size) could result in smaller PV plants, since the PV production increases in comparison to that with a fixed-tilt PV configuration.